Publisher Correction: Deubiquitinase Usp12 functions noncatalytically to induce autophagy and confer neuroprotection in models of Huntington’s disease - Rebecca Aron (Nature Portfolio, 2018)
The original version of this Article incorrectly gave a publication date of 8 October 2018; this should have been 28 September 2018. This has now been corrected in the PDF and HTML versions of the Article.